VISUALISASI PERAN USTAZ SALMAN DAN KIAI RAIS SEBAGAI PENDIDIK PADA FILM NEGERI 5 MENARA - Sarah Aulia Muchtar; Dedi Eko Nurcahyo (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
The drama genre drama Negeri 5 Menara was released in 2012 directed by Affandi Abdul Rachman. This study aims to find out how the role of Ustaz Salman and Kiai Rais as educators is visualized in the film Negeri 5 Menara. Researchers use qualitative methods. Primary data sources use original DVDs and secondary data from interviews with the director of the film Negeri 5 Menara as well as synopsis and film posters obtained from Sinematek Indonesia. Data collection techniques using observation, interviews and documentation. Data analysis was carried out in 3 stages, namely data reduction, data presentation, and drawing or verifying conclusions. The findings of this study focus on a directing approach that presents narrative elements, mise en scene and cinematography which shows the visualization of the role of Ustaz Salman and Kiai Rais as educators. The role of Ustaz Salman as an educator is visualized in scene 36, scene 45 and scene 71 and scene 72 while the role of Kiai Rais as an educator is visualized in scene 39,scene 57, scene 58, scene 61 and scene 62.